Antimicrobial resistance interventions in the animal sector: scoping review - Jacobsen, Alice B. J. E.; Ogden, Jane; Ekiri, Abel B. (Frontiers in Antibiotics, 2023)
Animals are considered key contributors to the development and spread of antimicrobial resistance (AMR). However, little is known about the existing AMR interventions in the animal sector and related environments. This scoping review examines the existing evidence on AMR interventions aimed at livestock, animal health professionals (AHPs), and farmers, while reviewing their impact, limitations, gaps, and lessons for future use. The scoping review was conducted following guidelines from the PRISMA-ScR checklist. The databases, Web of Science, Scopus, PubMed, and international organisations' websites (WHO, FAO, WOAH) were searched for articles reporting interventions targeting livestock, farmers, and AHPs. Interventions were categorised based on seven pre-defined primary measures including: change in antimicrobial use (AMU) practices; change in the uptake of antimicrobial stewardship (AMS); change in development of AMR; change in knowledge of appropriate AMU practices, AMR, and AMS; change in attitudes and perceptions concerning AMU, AMR, and AMS; and surveillance strategies. In total, ninety sources were included: 66 studies, 20 reports, and 7 webpages. The reviewed interventions focused mostly on AMU practices (22/90), AMS uptake (8/90), and reduction of bacterial or resistant strains (30/90). Changes in knowledge (14/90) and attitude (1/90) were less frequently assessed and were often implicit. Most interventions were conducted within a select country (83/90) and 7/90 were at a global level. Only 19% (16/83) of interventions were implemented in low-and middle-income countries (LMICs) and most were at herd level with many self-reporting changes. Most of the interventions that focused on surveillance strategies (30/83) were implemented in high-income countries (62/83). Only one study investigated the financial implications of the intervention. The study findings provide an overview of existing AMR interventions and insights into the related gaps which can be addressed used to guide future interventions and research. A focus on developing, implementing and evaluating interventions in LMICs coupled with the use of objective outcome measures (e.g., measurable outcomes vs. self-reporting) will improve our understanding of the impact of interventions in these settings. Finally, assessing the financial benefits of interventions is necessary to inform feasibility and to encourage uptake of interventions aimed at reducing AMR in the animal health sector.